Experience of Violence of Social Work Students in Field Studies: A Critical Review - Mariette, Natasha; Dhungel, Rita (Samriddhi Journal of Development Studies, 2023)
Social workers work with clients who are distressed, have unmet needs, or have complicated psychosocial issues (substance abuse, homelessness, a health-care crisis, intimate partner violence, etc.). The purpose of this critical analysis is to critically evaluate what is known about social work students' experiences with violence in field education. This critical review synthesizes the existing literature on the experiences of violent social work students during their fieldwork. The study's objectives are to: 1) what sorts of violence do social work students encounter during field education? 2) What training and education are required to respond to violence experienced by social work students in field education? To achieve the goals of this review, we critically examined seven relevant works through a postmodern feminism lens. We identified three major themes: social work as a gendered profession, diverse types of violence in field education settings, and a lack of violence prevention and safety training. A critical study, such as participatory action research with social work students in field education, as well as community-based research with field educators and supervisors, is advised. Furthermore, social work students must receive occupational health and safety training so that they can prepare for and respond to violence in their field studies. This study verifies social work's classification as a gendered profession.